Identifikasi Peptida Bioaktif dari Protein Kedelai sebagai Inhibitor Enzim Î±-glukosidase untuk Kandidat Antidiabetes - Fakih, Taufik Muhammad; Dewi, Mentari Luthfika (Universitas Muhammadiyah Surakarta, 2020)
Diabetes mellitus is one of the endocrine metabolic disorders that has caused morbidity and mortality worldwide. Î‘-glucosidase inhibitor which plays an important role in carbohydrate metabolism is needed to avoid postprandial hyperglycemia. A bioactive peptide derived from soy protein was chosen as an alternative treatment for diabetes because of its therapeutic potential. Several bioactive peptides have been shown to inhibit the Î±-glucosidase enzyme, such as the bioactive peptide LLPLPVLK, SWLRL, and WLRL. This study aims to identify and evaluate molecular interactions that occur between bioactive peptide molecules and Î±-glucosidase enzyme macromolecules using protein-peptide docking methods through in silico. Bioactive peptide sequencing was first modeled using the PEP-FOLD software. The best conformation was chosen for an interaction study of the Î±-glucosidase enzyme macromolecule using HPEPDock software. Further exploration was carried out on the molecular interactions formed using BIOVIA Discovery Studio 2020 software. Based on the results of molecular docking, the WLRL bioactive peptide has the best affinity against the Î±-glucosidase enzyme, with a binding free energy value of âˆ’748.12 kJ/mol. Therefore, the bioactive peptide is predicted to be a suitable candidate for the Î±-glucosidase enzyme inhibitor.